2003
DOI: 10.1063/1.1589196
|View full text |Cite
|
Sign up to set email alerts
|

Memory and negative photoconductivity effects of Ge nanocrystals embedded in ZrO2/Al2O3 gate dielectrics

Abstract: Metal–insulator–semiconductor (MIS) structures containing Ge nanocrystals embedded in high permittivity dielectrics (ZrO2/Al2O3) are fabricated by electron-beam evaporation method. Capacitance–voltage (C–V) and I–V characteristics of the fabricated MIS structures are investigated in the dark and under illumination. Charge storing and negative photoconductivity effects of the Ge nanocrystals are experimentally demonstrated by the hysteresis in the C–V curves and the decrease of the current under illumination at… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
27
0

Year Published

2004
2004
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 47 publications
(28 citation statements)
references
References 17 publications
0
27
0
Order By: Relevance
“…Recently, much efforts have been made to improve the device performance of nanocrystal memory by replacing the SiO 2 with various dielectrics such as oxynitride, 1 Al 2 O 3 , 2,3 ZrO 2 , 4 and SiN x . 5,6 King et al 7 demonstrated that a Ge nanocrystal memory device can be programmed at a relatively low voltage and high speed.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, much efforts have been made to improve the device performance of nanocrystal memory by replacing the SiO 2 with various dielectrics such as oxynitride, 1 Al 2 O 3 , 2,3 ZrO 2 , 4 and SiN x . 5,6 King et al 7 demonstrated that a Ge nanocrystal memory device can be programmed at a relatively low voltage and high speed.…”
mentioning
confidence: 99%
“…In our previous work, electric characteristics, and the negative photoconductivity of Ge nanoclusters embedded in Al 2 O 3 or in ZrO 2 /Al 2 O 3 gate dielectrics have been investigated. 2,4 Considerable attention is now being paid to HfO 2 8-10 as a gate dielectric due to its relatively high dielectric constant ͑high-k͒, large band-gap and proper band-offset. Results indicated that the use of high-k dielectric on Si as a tunnel layer offers a lower electron barrier height at the dielectric/Si interface and larger physical thickness, resulting in faster programming and longer retention than is found in a conventional SiO 2 tunnel layer.…”
mentioning
confidence: 99%
“…However, it is still difficult to fabricate uniform and self-organized Ge nanocrystals. Most of the methods, including the thermal annealing of Ge and dielectric mixture layer, [13][14][15] Ge ion implantation, 5 and the oxidation of SiGe, 6,7 require annealing at high temperatures. Baron et al 16 has fabricated Ge nanodots on the SiO 2 matrix by low-pressure chemical vapor deposition.…”
mentioning
confidence: 99%
“…The memory effect of the Ge nanocrystals with storage charge density of up to 10 12 The nanocrystal floating gate embedded in dielectrics has attracted a great deal of attention recently because it can potentially be applied in nonvolatile, high-speed, highdensity, and low-power consuming memory. [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15] Compared to conventional floating gate memories such as flash, a device composed of nanocrystals isolated by dielectrics benefits from a relatively low operating voltage, high endurance, fast write-erase speeds, and better immunity to soft errors. 1 For the first nano-floating-gate memory, the materials of nanocrystals and dielectrics were Si and SiO 2 , respectively.…”
mentioning
confidence: 99%
See 1 more Smart Citation